Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Menabung pada Produk Tabungan Mudharabah di KSPPS BMT NU Cabang Camplong - Faruq, Umarul; Jennah, Nurul (Faculty of Islamic Economics and Business, Madura Islamic State University, 2023)
The development of Islamic financial institutions, such as the KSPPS BMT NU Camplong Branch, is growing rapidly. In order to remain competitive, they need a good marketing strategy. One of them is by paying attention to the quality of service and products. If the service and products are of good quality, customers will be interested in saving. Therefore, this research aims to examine the influence of service quality and product quality on customers' saving decisions for Mudharabah Savings products at the KSPPS BMT NU Camplong Branch. This research uses a quantitative method with statistical analysis. The population of this study consists of all customers of Mudharabah Savings at the KSPPS BMT NU Camplong Branch, totaling 3555 customers. The research sample was taken using the Accidental Sampling method, with a total of 98 customers. The results of the study show that service quality and product quality have a significant influence on customers' saving decisions. Overall, 47.9% of customers' saving decisions can be explained by the variables of service quality and product quality.